Sosialisasi Pembuatan Lubang Biopori Sebagai Upaya Pencegahan Banjir Di Kampung Rawa Mekar Jaya Kecamatan Sungai Apit - Efriyeldi Efriyeldi; Ahmad Pasmuji; Abiyu Rohid; Muhammad Farhan; Friska Maulidah; Safatriani Safatriani; Vichi Apridianti; Nadiyatus Sholihat; Rifda Syofiana R; Cut Shifa Nedi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This community service program was carried out in Rawa Mekar Jaya Village, Sungai Apit District, Siak Regency. This program was implemented with the aim of providing knowledge about the benefits of making biopore holes as well as to educate and increase public understanding of biopore holes to prevent flooding. The methods used in this community service activity are lectures and discussions directly involving all the service teams and all the Rawa Mekar Jaya village officials, the Rawa Mekar Jaya community and students of the Riau University Real Work Lecture (Kukerta) Academic Year 2023. To find out understanding Participants were evaluated on the material presented by asking participants to fill out a questionnaire before and after the activity. The data obtained was analyzed descriptively. The results of this service activity show that all participants participated in the series of activities well from start to finish. Service participants can understand the material presented well. As many as 80% of participants were able to understand how to make biopore holes, 70% of participants knew that biopore holes could be used to absorb rainwater, indicated by the absence of standing water and the decomposition of waste put into the hole. All 100% participants before the service was carried out, no one had made biopore holes. This means that all new participants made biopore holes after this service activity. This service activity has gone well, marked by the participants knowing how to make biopore holes.